2017
DOI: 10.3389/fphys.2017.00013
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Signaling Pathways in Insulin Resistance-Systems Biology Analyses of Microarray Dataset Reveals New Drug Target Gene Signatures of Type 2 Diabetes Mellitus

Abstract: Purpose: Type 2 diabetes mellitus (T2DM) is a chronic and metabolic disorder affecting large set of population of the world. To widen the scope of understanding of genetic causes of this disease, we performed interactive and toxicogenomic based systems biology study to find potential T2DM related genes after cDNA differential analysis.Methods: From the list of 50-differential expressed genes (p < 0.05), we found 9-T2DM related genes using extensive data mapping. In our constructed gene-network, T2DM-related di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Our prediction on seasonality was supported; we found that temperature positively affected the activity of Japanese macaques during the studied year, indicating that macaques were more active when the thermal conditions were favorable. The thermoneutral zone, i.e., the ambient temperature range that does not require animals to allocate additional energetic costs to thermoregulation, is reported to be 5–28°C for colobus monkeys [ 49 ], 20–27°C for titis [ 50 ], 25–30 for tarsiers [ 51 ], 25–32°C for sportive lemurs [ 52 ], above 27°C for mouse lemurs [ 53 ], 27–34°C for pygmy marmosets [ 54 ] and 17–28°C for chimpanzees [ 55 ]. Even though the thermoneutral zone for macaques has not been reported, a feeding experiment on captive macaques indicated that they changed food intake and food selection when room temperature decreased from 29 to 15°C [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our prediction on seasonality was supported; we found that temperature positively affected the activity of Japanese macaques during the studied year, indicating that macaques were more active when the thermal conditions were favorable. The thermoneutral zone, i.e., the ambient temperature range that does not require animals to allocate additional energetic costs to thermoregulation, is reported to be 5–28°C for colobus monkeys [ 49 ], 20–27°C for titis [ 50 ], 25–30 for tarsiers [ 51 ], 25–32°C for sportive lemurs [ 52 ], above 27°C for mouse lemurs [ 53 ], 27–34°C for pygmy marmosets [ 54 ] and 17–28°C for chimpanzees [ 55 ]. Even though the thermoneutral zone for macaques has not been reported, a feeding experiment on captive macaques indicated that they changed food intake and food selection when room temperature decreased from 29 to 15°C [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics, including nucleic acid sequence analysis, protein sequence analysis and genomics, can be used to collect, process, store, classify, analyze and interpret biological information through the application of mathematics and computer technology. For example, when combined with microarray technology, bioinformatics analysis can identify the connection between meaningful molecular interactions and evaluate the associated signaling pathways ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance has been described as an early stage in the pathogenesis of glucose intolerance and T2DM [59]. Therefore, we assessed a possible relationship between ADIPOR1/2 variations, serum insulin concentrations, and HOMA-IR in the present study.…”
Section: Discussionmentioning
confidence: 96%